3,472 UMP students receive student devices - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 30 October 2022 - A total of 3,472 students of Universiti Malaysia Pahang (UMP) received student devices in stages through the Keluarga Malaysia Student Device Programme, which is a government initiative to assist students from the B40 group in ensuring that their study process runs smoothly.